The Effect of Online Shopping and E-Wallet on Consumer Impulse Buying - Sari, Risca Kurnia; Utama, Satria Putra; Zairina, Anisa (APMBA (Asia Pacific Management and Business Application), 2021)
This research examines the influence of On-line Shopping and E-wallet on Impulse Buying. The existence of an online shopping phenomenon using digital wallet payments (e-wallets) is prevalent among the public recently. This study adopted a survey method with 200 respondents selected purposively from two large cities in East Java, Indonesia namely malls located in Malang and Surabaya. Using variables that consist of shopping variables consisted of: variety of choices, price level, sensory attribute, utilitarian browsing, and hedonic browsing. Moreover the E-wallet variables consist of: effect of service features, advertising, benefit perceptions, perceived usefulness, consumer attitude, security, risk, and discount. Findings revealed that price level, hedonic browsing, benefit perceptions, perceived usefulness, consumer attitude, security, risk, and discount had a significant positive correlation with impulse buying; while the variety of choices, utilitarian browsing, effect of service features, and advertising had a significant negative correlation with impulse buying. Online shopping and e-wallet variables simultaneously affect impulse buying. Practical implications are also discussed in this article.Â